Larvae identification and development of the only freshwater Sardinella, Sardinella tawilis endemic to Taal lake, Philippines - Mutia, Maria Theresa M.; Sarmiento, Katreena P.; Muyot, Myla C.; Mendiola, Michael John R.; Tordecilla, Benjie D.; Santos, Mudjekeewis D. (2017)
Philippines, continues to be an important food commodity and serves as a piece of cultural heritage within the country. However, the early life history of this species is unknown. In the present study, identification of the S. tawilis larvae has been finally confirmed through the utilization of the DNA barcode marker cytochrome c oxidase I (CO1) gene and the Kimura 2-parameter (K2P) distance model. Results showed 100% identity of three larvae samples with S. tawilis GenBank reference sequences based on clustering analysis, which was supported by mean genetic distance of 1%, suggesting accurate identification of the larvae samples. Subsequently, the larval developmental stages in pre-flexion, flexion, post-flexion and juvenile stage of S. tawilis were described and illustrated. Morphological analyses revealed that the larvae had elongated and straight gut with budding pectoral fin during pre-flexion stage, disappearance of fin-fold on the flexion stage, growth of fin rays during post-flexion stage and well developed fins in juvenile stage. This study serves as the first report on the identification of S. tawilis larvae as well as its morphological description during larval development. (Author's abstract)